Research on Motor Transport Produced Noise on Gravel and Asphalt Roads - Linas Leipus; Donatas Butkus; Tomas Januševičius (The Baltic Journal of Road and Bridge Engineering, 2010)
Vehicles in motion on roads are the main source of noise in the environment. The noise in a car is created by structural noises from car construction, originated from vibrations in an engine, cabin, silencer, wheels and tires. Traffic noise flow depends on its intensity, motion speed, flow composition and extent, quality of the road pavement and build-up of the area along the road. This paper contains research on motor transport produced noise levels on roads of regional signifi cance with gravel and asphalt pavement in Molėtai district. The level of motor transport produced noise was measured in wintertime and summertime at the chosen typical locations considering the nature of the asphalt and gravel road pavement and diff erent landscape morphology forests, topography roughness, open area, upslope, downslope, etc. Also, research of noise level dependence on car speed was performed from 50 km/h to 70 km/h. It was determined during the study that noise level produced by a car moving at a speed of 50 km/h on a road with gravel pavement is higher by 4 dBA than that on a road with asphalt pavement. Upon moving away from the noise source by 50 m, the level of noise decreases by 12 dBA in woodland open areas and by 16 dBA. As car speed increases from 40 km/h to 50 km/h in wintertime, the level of noise rises by 2 dBA. In summertime, as car speed increases from 50 km/h to 70 km/h, the noise level rises by 5 dBA. These differences are due to the presence of ice and snow on the road in winter. Noise depends on physical properties of tires, type of pavement, car vibrations and in particular on pavement roughness.